1983
DOI: 10.1099/0022-1317-64-6-1421
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of Eel Virus European

Abstract: SUMMARYThe polypeptide and RNA compositions of purified virions of eel virus European were compared to those of three strains (VR-299, SP and AB) of infectious pancreatic necrosis virus (IPNV) isolated from trout. All three IPNV strains could be distinguished by the relative mobilities of either the virion polypeptides or the doublestranded RNA genome segments. The eel virus had a similar polypeptide profile to strain AB IPNV but differences between the two viruses in the migration of genome segments indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

1984
1984
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 16 publications
0
22
1
Order By: Relevance
“…Virus purification was similar to that previously described for IPNV (Hedrick et al 1983). Briefly, virus isolates were propagated using the Chinook salmon Oncorhynchus tshawytscha embryo cell line (CHSE-214) (ATCC CRL 1691).…”
Section: Methodsmentioning
confidence: 99%
“…Virus purification was similar to that previously described for IPNV (Hedrick et al 1983). Briefly, virus isolates were propagated using the Chinook salmon Oncorhynchus tshawytscha embryo cell line (CHSE-214) (ATCC CRL 1691).…”
Section: Methodsmentioning
confidence: 99%
“…EVE and IPNV type Ab were also found to be similar in polypeptide and RNA composition, and clearly distinguishable from IPNV strains VR-299 and Sp (T. Sano et al 1981, Hedrick et al 1983a. Using cross-neutralisation assays with almost 200 IPNV isolates, Hill & Way (1995) later proposed a new serological classification, consisting of serogroup A containing serotypes A1 to A9, and serogroup B containing the single serotype B1.…”
Section: Eel Virus European Aetiologymentioning
confidence: 97%
“…Electron microscopy (EM) revealed that EVE virions were non-enveloped polyhedrons with a diameter of 68 to 77 nm, only present in the cytoplasm of infected cells. EVE also resembled IPNV in terms of biological properties, such as polypeptide composition and the bisegmented double-stranded RNA genome (Nishimura et al 1981a, T. Sano et al 1981, Hedrick et al 1983a Lee et al 1999aLee et al , 2001.…”
Section: Eel Virus European Aetiologymentioning
confidence: 99%
See 2 more Smart Citations